Effects of poling camber angle on the biomechanics of cross-country sit-skiing - Y. Tian; X. Chen; Y. Liu; G. Sun; Z. Zhou; C. Liu; B. Huo (Scientific Reports, 2023)
Cross-country sit-skiers use double poling (DP) technique to drive the slide. The aim of this study is to analyze how poling camber angle affect the capacity of power output and biomechanical parameters of the DP process. Twenty-four non-disabled college students (24.67 ± 1.46 years old) were recruited to perform three successive 30-s maximal effort tests with different poling camber angles of 0°, 15°, 24° and 30° using a sit-skiing ergometer. The biomechanical parameters, output power and muscle activation of the subjects were analyzed. The results showed that DP output power increased with the increase of poling camber angle at 15° (597.78 ± 150.31 J), 24° (610.94 ± 158.96 J, P = 0.011) and 30° (629.10 ± 168.78 J, P < 0.001) compared with 0° (590.65 ± 148.95 J). However, effective output power decreased with the increase of camber angle. Poling with camber angle of 24° had the shortest cycle time 1.53 ± 0.17 s, compared with other abduction angle (0°, 1.57 ± 0.19 s, 15°, 1.55 ± 0.16 s, and 30°, 1.56 ± 0.19 s). Compared with 0° (1.02 ± 0.14 m), the cycle distance significantly increased at poling camber angles of 24° (1.07 ± 0.12 m, P = 0.029) and 30° (1.11 ± 0.13 m, P < 0.001). With the increase of poling camber angle, the shoulder and elbow joint range of motions and joint moments were significantly increased. This study found that poling with shoulder abducted increased the output power but decreased the efficiency. By analyzing the poling angle and poling force, we find that the optimal poling camber angle may depend on the terrain or the skiing speed. These results may guide the competition techniques and tactics in the matches, and may further influence the strength-training programs of cross-country sit-skiing athletes.